Genealogy of the Shchedrins Family and the New Biographic Data on Some of Its Representatives - Evsevyev, Mikhail Iu.; Sokhor, Tatyana E. (Actual Problems of Theory and History of Art, 2018)
This article deals with the verification of sources on the birth date of Sylvestr Feodosievich Shchedrin for the first time. The analysis of the data obtained from the various studies on the artist’s biography has been introduced in the present research. Those members of the Shchedrins family who were the brightest in artistic respect are built into the project of their genealogical tree. The new materials that were found in federal and regional archives are used as tools to determine diverse connections of the Shchedrins with the artists who belonged to the Academy of Fine Arts’ circle in general and with the family of Ivan Petrovich Martos in particular.The newly found materials allowed adding unknown Moscow relatives from the Pesche family to Shchedrins’ genealogical tree. The detailed study of the history of matrimonial relationship between Fedos Shchedrin and Maria Petrovna Pesce has been introduced for the first time in this work. The previously unknown facts from the master’s life in the second half of the 1780s were discovered during the study of Ekaterina II’s correspondence.They revealed F. F. Shchedrin’s involvement into the formation of the collection of cameos for the Empress as well as his participation in the acquisition and delivery of the Diderot’s library to St. Petersburg. The records on Fedos Shchedrin that were found in the Russian State Historical Archive and that identified his work on sculptural portraits of the Empress made it possible to confirm his close relation to the Imperial court as well as to introduce another original work by the master for the scientific study.
Keywords: genealogy; Sylvestr Shchedrin; Fedos Shchedrin; source study of art history; Academy of Fine Arts; I. P. Martos; Ekaterina II; M. P. Pesche